2021
DOI: 10.1021/acsomega.1c04316
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Significance of Catalytic and Alkyl Exchange Reactions during GaAs and GaP Growth by Metal Organic Vapor Phase Epitaxy

Abstract: Tertiarybutylarsine (TBAs) and tertiarybutylphosphine (TBP) are getting more and more established as group V precursors for the growth of V/III semiconductors by metal organic vapor phase epitaxy (MOVPE). Due to this development, the thermal decomposition of these precursors was studied during the growth of GaAs and GaP utilizing the Ga precursors, trimethylgallium (TMGa), triethylgallium (TEGa), and tritertiarybutylgallium (TTBGa), in a horizontal AIXTRON AIX 200 GFR MOVPE system. The decomposition and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…It is reported that the formation of C 4 H 10 and •C 4 H 9 in the lower temperature regime is superseded by C 4 H 8 with increasing temperature. [ 16,17 ] Maßmeyer et al. observed the same decomposition products and suggested the reaction pathways of homolytic fission, intramolecular coupling, and β‐hydrogen elimination.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…It is reported that the formation of C 4 H 10 and •C 4 H 9 in the lower temperature regime is superseded by C 4 H 8 with increasing temperature. [ 16,17 ] Maßmeyer et al. observed the same decomposition products and suggested the reaction pathways of homolytic fission, intramolecular coupling, and β‐hydrogen elimination.…”
Section: Resultsmentioning
confidence: 84%
“…Extrapolating the PH 3 curve reveals that decomposition begins at a membrane temperature of (640 ± 20) °C, which aligns with the susceptor temperature of TBP decomposition in MOVPE reactors. [ 17 ] Consequently, the relationship between gas‐phase temperature and membrane temperature in the in situ TEM holder is comparable to that of gas‐phase temperature and susceptor temperature in conventional MOVPE reactor designs. With rising temperature, the amount of decomposed TBP increases continuously.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For the latter challenge, in situ control during the preparation and operation is desired, for example, with benchmarking of in situ signals via interfacial characterization. [358,359] New III-V compounds involving nitrogen or boron for high-efficiency multijunction solar cell components may advance the portfolio of suitable materials. [360][361][362] To prepare III-V compounds, less hazardous, nongaseous, and more efficient precursor molecules should be employed such as tertiarybutylphosphine (TBP) instead of phosphine (PH 3 ), ditertiarybutylsilane (DTBSi) instead of silane (SiH 4 ), and tertiarybutylarsine (TBAs) instead of arsine (AsH 3 ).…”
Section: Iii-v Compoundsmentioning
confidence: 99%